THE EFFECT OF BLENDED LEARNING USING SCHOOLOGY TOWARD STUDENT LEARNING OUTCOMES - Aulia Syafrianti; Makmur Sirait (INPAFI (Inovasi Pembelajaran Fisika), 2022)
This study aimed to determine the effect of blended learning using schoology toward student learning outcomes. The type of research is quasi-experiment. The population of this study is all students of class X MIA in MAN 1 Medan in the second semester of A.Y 2019/2020 which consisted of 9 classes. By purposive sampling technique selected class X MIA 1 as the experiment class has given blended learning treatment using schoology and X MIA 4 as the control class has given conventional learning treatment. The total students in both classes are the same, 30 students, the total sample is 60 students. The instrument used is a multiple-choice test of 20 questions with 5 choice answers validated by the validator. The results showed the average value of the experiment class pre-test is 51.83 and the control class is 50.67. In the normality and homogeneity test of the two classes, it is found that the data of both classes distribute normal and homogeneous. By using two tail t-tests can be stated that the initial abilities of students of both classes are the same. After treatment in each class, the average value of the post-test experiment class is 81.67 and the control class is 66.67. In the normality and homogeneity test obtained that the data of both classes are normally distributed and homogeneous. By using one tail t-test can be stated that there is a significant effect of blended learning using schoology toward student learning outcomes.